Test and Analysis of the Optical Kerr-Effect in Resonant Micro-Optic Gyros - Xuehui Li (IEEE Photonics Journal, 2014)
As one kind of the main optical error sources in the resonant micro-optic gyro (RMOG), the optical Kerr-effect brings a nonzero bias to the output of the RMOG. The optical Kerr-effect induced bias error is proportional to the difference between the clockwise (CW) and counterclockwise (CCW) light-intensities input to the resonator. A new method for testing the optical Kerr-effect induced bias error in the RMOG is proposed and demonstrated. A square-wave intensity-modulated optical signal with a symmetrical duty ratio of 50% is achieved by an acousto-optic modulator (AOM), thus making the input-intensity mismatch between the CW and CCW lightwaves change periodically. In this way, we obtain the optical Kerr-effect induced bias errors that vary periodically in accordance with the variation of the square-wave signal. The experimental results show a good agreement with the theoretical value. Moreover, the testing result of the closed-loop RMOG is consistent with the open-loop one. The above method is insusceptible to other noise, such as the backscattering-induced noise and the polarization fluctuation.